The Spectrum of Translation in Cortázar’s “Letter to a Young Lady in Paris" - Guzmám, María Constanza (Íkala, Revista de Lenguaje y Cultura, 2006)
Translation is a recurrent theme in Julio Cortazar’s fiction. In this paper, his short story "Letter to a Young Lady in Paris" is presented as a story about translation in which the protagonist, who comes to inhabit a space temporarily, "invades" that space subverting the original order. This representation is discussed in relation to prevailing notions about translation and translators. Received: 06-04-06 / Accepted: 24-07-06 How to reference this article: Guzmán, M. C. (2006). The Spectrum of Translation in Cortázar’s “Letter to a Young Lady in Paris”. Íkala. 11 (1), pp. 75 – 86